PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE CARD SORT (KARTU SORTIR) UNTUK MENINGKATKAN AKTIVITAS DAN KETUNTASAN BELAJAR SISWA PADA POKOK BAHASAN KOLOID DI KELAS XI IPA 1 SMAN 3 PEKANBARU - Dewi, Resya Sukma; Amran, Elva Yasmi; Haryati, Sri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Classroom action research has been done on student’s activity and learning mastery on colloid subject in XI IPA 1 of SMAN 3 Pekanbaru. This research was conducted by applying active learning strategy of Card Sort. Improved student learning activity is the activity of asking questions, submit answers or opinions, working on exersices and group discussion, evaluation too.This research consisted of two cycles. Each cycle consisted of one meeting through four stages of implementation: planning, action, observation, and reflection. Data collection techniques using observation and test. The result of action showed that activity percentage of students increased and reached the success indicator. Activity of student percentage in first cycle 57,89% with criteria enough and second cycle 71,85% with criteria good. The percentage of learning outcomes also increased and reached the success indicator. The average percentage in first cycle 68,57 and second cycle 85,71% . Based on the result obtained, it can be concluded that application active learning strategy of Card Sort can increase student’s activity and learning mastery.Keyword: Active Learning of Card Sort, Learning Activities, Learning Mastery